IMPLEMENTASI PRINSIP GOOD GOVERNANCE DAN PERANANNYA DALAM PROSES KEPAILITAN - FAKHRURRAZI FAKHRURRAZI (POLITEKNIK PIKSI GANESHA, 2019)
This study aims to determine the implementation of the principles of good governance and its role in the bankruptcy process. This research method is quantitative. The results showed that corporate governance with the basic principles of good corporate governance, companies that apply the principles of good corporate governance have healthy business prospects, consistent implementation has the potential to resolve the company's obligations to its creditors and Islamic bankruptcy legal principles basically provide protection to debtors and creditors, but it indicates protection to creditors takes precedence over debtors.